The Application of a Gamification Approach to Enhance Motivation in Learning Mathematics Among Fourth-Grade Elementary School Students - Belda Nurmultiefa; Daryaman; Dean Monika; Dhea Dwi Rahmawati; Ega Ariswati (Journal of Asian Primary Education (JoAPE), 2026)
Learning motivation is a crucial factor that determines the success of mathematics learning at the elementary school level. However, low motivation remains a persistent challenge, particularly in schools with limited access to digital technology. This study aims to analyze the effectiveness of the gamification approach in improving mathematics learning motivation among Grade IV students at SD Negeri 2 Mekarmukti. Grounded in Self-Determination Theory (Deci & Ryan, 2000), which posits that intrinsic motivation develops through the fulfillment of three basic psychological needs (competence, autonomy, and relatedness), this study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model across two cycles. Subjects were 25 Grade IV students during the even semester of the 2025/2026 academic year. Data were collected via observation sheets, a 45-item learning motivation questionnaire (1-5 Likert scale), and documentation, then analyzed using descriptive quantitative techniques. Findings show that the mean motivation score increased from 26.80 (pre-cycle) to 32.12 (Cycle I) and 35.36 (Cycle II), while the proportion of students in the highly active category rose from 32% to 64% and ultimately to 92%, surpassing the 85% success threshold. The most effective gamification elements were structured group challenges with clear rules (Mystery Card Quest and Flashcard Sprint), point systems, and reward mechanisms. This study demonstrates that non-digital, activity-based gamification is an accessible and effective strategy for elementary school teachers in resource-constrained settings.